2014
DOI: 10.1136/annrheumdis-2013-204116
|View full text |Cite
|
Sign up to set email alerts
|

Expression of FcRL4 defines a pro-inflammatory, RANKL-producing B cell subset in rheumatoid arthritis

Abstract: ObjectivesThe success of B cell targeting therapies has highlighted the importance of B cells in rheumatoid arthritis pathogenesis. We have previously shown that B cells in the RA synovium are capable of producing pro-inflammatory and bone-destructive cytokines including RANKL. Here we sought to characterise the nature and functional relevance of the RANKL-producing B cell subset in the RA synovium.MethodsSynovial fluid and peripheral blood B cells from patients with RA were analysed by flow cytometry for mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 26 publications
11
86
1
1
Order By: Relevance
“…FcRL4 dampens BCR activation, but enhances TLR9 signaling, favoring a switch from adaptive to innate B cell signaling (51). Moreover, a recent study has shown that tissue-FcRL4 + B cells produce proinflammatory cytokines like IL-6, TNF, and receptor activator for NF-kB ligand in rheumatoid arthritis (52). We have shown a good correlation of active typical MBC with proinflammatory IL-8 and TNF, higher IL-8 plasma levels in exposed versus unexposed donors, and higher TNF levels in EP versus NP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…FcRL4 dampens BCR activation, but enhances TLR9 signaling, favoring a switch from adaptive to innate B cell signaling (51). Moreover, a recent study has shown that tissue-FcRL4 + B cells produce proinflammatory cytokines like IL-6, TNF, and receptor activator for NF-kB ligand in rheumatoid arthritis (52). We have shown a good correlation of active typical MBC with proinflammatory IL-8 and TNF, higher IL-8 plasma levels in exposed versus unexposed donors, and higher TNF levels in EP versus NP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…They also proliferate poorly in response to B cell stimuli. A similar CD21 2/lo B cell population is expanded in other chronic infections and inflammatory conditions where the immune system encounters increased Ag load for a prolonged period of time, such as chronic malaria (5), systemic lupus erythematosus (6), type Ia common variable immunodeficiency (CVID Ia) (7,8), rheumatoid arthritis (8,9), and Sjögren's syndrome (10). Additionally, TLM B cells accumulate in patients with germline heterozygous mutations in CTLA4 (11).…”
Section: T He Generation Of B Cell Memory Is An Important Component Omentioning
confidence: 99%
“…FCRL4 is unique in that it is expressed exclusively by a limited population of Bmem cells that are normally based in mucosal lymphoid tissues (5). Interestingly, an exhausted population of FCRL4 + Bmem cells has been detected in blood samples from viremic HIV-1 + individuals, as well as in individuals from malaria-endemic regions (12)(13)(14) and in the joint fluid of rheumatoid arthritis patients (15).…”
mentioning
confidence: 99%